ANALISIS KAUSALITAS UTANG LUAR NEGERI, PENGELUARAN PEMERINTAH SERTA PEREKONOMIAN INDONESIA DAN MALAYSIA - Rafizjah Juria Absa; Hasdi Aimon (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to identify and analyze the causality of relationship between, analyze the causality of foreign debt, government expenditure and economy Indonesia and Malaysia. This type of research is associative descriptive research, where the data used are secondary data from data time series from 1987 to 2016 that use data Vector Error Correction Model (VECM). foreign debt as one of the pillars of development. the Indonesian government budget places foreign debt as a shortage component. Foreign debt as one of the pillars of development. the Indonesian government budget places foreign debt as a shortage component. to regulate the economy by determining the amount of government revenue and expenditure each year in the APBN. The economy is the production of goods and services produced by each country.